Semiotic of the Mejdoub representations in the local society - hamida, abdelkader (Journal of Social Sciences and Humanities, 2024)
The Djedb is a kind of madness which is sanctified in Arab Islamic societies in general, and in North Africa in particular, and in Sufis it is a “makam”, which some of them have called “mystical madness”. And because this madness is multidimensional, cultural and social, the representations are also multiple and complex, and to understand some of these representations which are manifested well in these spaces, and well reflect the socio-cultural identity of the Majdoub, we have choose the space of Majdoub Sheikh Abderrahman Naas Bouragba (1905-1993), because of its sociological importance, because his dunamism is still in progress, and the mechanisms of domination and submission are are always produced and reproduced (As if the sheikh was alive and present in his room). And to arrive at this understanding, we adopted three basic approaches, the first of which is the so-called “symbolic” approach of Pierre Bourdieu (1930-2002), which helped us to draw the parameters of domination and submission in the space, using the most important concepts such as “Symbolic Capital,” “Reproduction”, “Symbolic Authority” and “Habitus”, and the second is the semiotic approach according to Charles Sanders Pierce (1839-1914), represented by "representation - communication - meaning" which formed the structure of our analysis, and at the end we also convened the third approach which we can call the theory of "social representations", according to the approach of Jean Claude Abric (1941-2012), or the “Central Core” thesis, which allowed us to take into account the different sociological manifestations of the Mejdoub, such as his clothes, his body and his photos.